2016
DOI: 10.1164/rccm.201509-1863oc
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin Variants Are Associated with Idiopathic Pulmonary Fibrosis

Abstract: Rationale: Sequence variation, methylation differences, and transcriptional changes in desmoplakin (DSP) have been observed in patients with idiopathic pulmonary fibrosis (IPF).Objectives: To identify novel variants in DSP associated with IPF and to characterize the relationship of these IPF sequence variants with DSP gene expression in human lung.Methods: A chromosome 6 locus (7,370,606,946) was sequenced in 230 subjects with IPF and 228 control subjects. Validation genotyping of disease-associated variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 28 publications
3
68
0
1
Order By: Relevance
“…Aberrant activation of Wnt/␤-catenin signaling pathway has been implicated in the development of pulmonary fibrosis (6) and is, thus, one potential mechanism for a profibrotic role of DSP in IPF. Interestingly, increased DSP gene expression was demonstrated in lung tissue of IPF patients without the DSP gene variant rs2076295 (36). This increase could be the consequence of epithelial cell injury-repair response to maintain epithelial barrier integrity in response to persistent epithelial injury.…”
Section: Genetic Variants Affecting Epithelial Cell Integritymentioning
confidence: 97%
See 1 more Smart Citation
“…Aberrant activation of Wnt/␤-catenin signaling pathway has been implicated in the development of pulmonary fibrosis (6) and is, thus, one potential mechanism for a profibrotic role of DSP in IPF. Interestingly, increased DSP gene expression was demonstrated in lung tissue of IPF patients without the DSP gene variant rs2076295 (36). This increase could be the consequence of epithelial cell injury-repair response to maintain epithelial barrier integrity in response to persistent epithelial injury.…”
Section: Genetic Variants Affecting Epithelial Cell Integritymentioning
confidence: 97%
“…This was shown to be due to disruption of mechanical linkage between cells and modifications to cell-cell adhesion proteins. The minor allele of variant rs2076295 in intron 5 has been associated with decreased whole lung DSP expression and higher risk of IPF (8,36). The differential expression of DSP in association with this variant suggests that disruption of desmosomal integrity with resultant impairment of cell-cell adhesion and aberrant epithelial barrier injury-repair response may participate in the development of IPF.…”
Section: Genetic Variants Affecting Epithelial Cell Integritymentioning
confidence: 99%
“…Similarly, DSP (desmoplakin) variance (rs2076295) is associated with increased risk of IPF. MUC5B and DSP expression in the lung, especially in the airway epithelium, indicates the contribution of the aberrant epithelium in IPF [11].…”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%
“…Analysis of expression profiles in a murine model of lung fibrosis induced by bleomycin showed enrichment in genes associated with cell junction organization and cell-substrate junction assembly during both the inflammatory and the fibrotic phases (8). In a genomewide association study, Fingerlin et al identified polymorphisms in the desmoplakin gene, another plakin family member, as a potential genetic risk factor in IPF (9,10). Mechanisms by which cell junctions ensure epithelium integrity during fibrogenesis remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%